BLOCKCHAIN TECHNOLOGY IN ELECTIONS: EXPLORING POTENTIAL AND IMPLICATIONS - Khaldun, Ibnu (Universitas Padjadjaran, 2025)
This study aims to explore the potential and implications of implementing blockchain technology in the context of elections and governance. Utilizing a mixed-method approach, including expert interviews, stakeholder surveys, and case studies from various countries, the research provides in-depth insights into how blockchain can revolutionize electoral processes and governance. The findings indicate that blockchain implementation in elections has the potential to enhance the integrity and security of voting processes, though significant challenges exist in terms of existing technological infrastructure and public acceptance. In governance, blockchain offers improvements in transparency and efficiency, yet faces obstacles in scalability, integration with existing IT systems, and data security and privacy. The study also reveals an urgent need for the development of appropriate legal and regulatory frameworks to support blockchain implementation while ensuring data security and privacy. The conclusion emphasizes the importance of a holistic approach and public education in deploying blockchain in the public sector to achieve beneficial and sustainable changes in the digital era. This research contributes significantly to the literature on blockchain, particularly its application in elections and governance, and provides guidance for policymakers and practitioners in effectively integrating this technology.